PARTICULARITIES OF WHITE HEAD CABBAGE F1 HYBRID BREEDING FOR PRIDNESTROVIAN MOLDAVIAN REPUBLIC CONDITIONS - L. I. Shpak; G. F. Monakhos (Овощи России, 2016)
A model of late maturing F1 hybrid of white head cabbage for long-term storing and suitable for national recipe “golubci” have been developed based on requirements for varieties and F1 hybrids grown in the South in the conditions of drought, high temperatures and low air humidity. Combining ability of seven self-incompatible inbred lines of white head cabbage was studied by the system of full diallel crosses in conditions of Pridnestrovian Moldavian Republic. These lines were developed on the base of heat tolerant varieties ‘Biruchekutskaya’, ‘Volna’, ‘Lada’, ‘Moldavanka’ and ‘Kharkovskaya Zimnyaya’ bred in the south. Out of 42 hybrid combinations studied 15 significantly surpassed in productivity the variety ‘Zavadovskaya’ that is traditionally grown by local farmers for pickling and recipe “golubci”. High GCA effects for productivity showed the following breeding lines: Bu1, Ml3 and Kl5. Polygenes, controlling the high yield ability, mainly were dominant and single-directed, however the correlation betweenyield ability and GCA effect was middle, r=0.63±0.35. No correlation was observed inbreeding line between GCA effect and truly heterosis effect in hybrid combinations (r=0.19). Disease resistance analysis revealed lines Bu1 and Kl5 that had shown resistance to Fusarium yellows. Two hybrid combination Kl5xBu1 and Ml3xBu1 were highly tolerant to thrips attacks according to analysis of all promising hybrid combinations, carried out in natural infection background. Weak correlation was observed between the number of damaged leaves in cabbage head and dry matter content, r=0.41±0.21, and also there is no correlation revealed with sugar contents, ascorbic acid and nitrate content. High tolerance of hybrids with participation of line Bu1 explained the partial dominance nature of the trait. Hybrid combinations Kl5xBu1 and Ml3xBu1 called ‘Batal’ and ‘Shedevr’, respectively, included in registry of Moldova and PMR.